Rett Syndrome. A Review with Emphasis on Clinical Characteristics and Intervention - Meir Lotan; Bruria Ben-Zeev (The Scientific World Journal)
Rett syndrome (RS) is a genetic disorder affecting mainly females. In the majority of cases, it is caused by a mutation in MECP2, an X-linked gene, and considered the most common multidisabling genetic disorder in females after Down syndrome. This article is an introduction to RS. It presents the basic understanding of common characteristics typical of this disorder, and the variants from the classical expression of RS. The present article will review the current literature on RS, specially focusing on the clinical characteristics of the disorder. The intention of the article is to set a clear, up-to-date picture of the individual with RS to prepare the clinician for their future meetings with this population.